Effect of operating parameters on haulage performance of 2WD tractor-trailer systems - Sahu, R K; Pandey, K P (Journal of Agricultural Engineering, 2005)
Field experiments were conducted with a 23 kW brake horsepower 2WD tractor using unbalanced and balanced trailer separately to know the effect of operating parameters such as gear, throttle position, payload and type of surface on haulage performance of the tractor-trailer systems. Tests were carried out in first high (1H) and second high (2H) gears at half and full throttle positions on three different surfaces namely tarmacadom, moram and firm grass surface. The payload was varied from 0 to 2800 kg for the unbalanced trailer and 0 to 4200 kg for the balanced trailer in four steps. Two spring dynamometers and an auxiliary fuel tank were used for measurement of draft, vertical force and fuel consumption. It was observed that with increase in payload, draft as well as vertical force increased in the unbalanced trailer. On the contrary, the vertical force was found to decrease with increase in payload in the balanced trailer. The draft requirement of a 2WD tractor with an unbalanced trailer was less than that with a balanced trailer on different terrain surfaces for the same payload. On the other hand the vertical force at hitch point was quite high in case of unbalanced trailer. The fuel consumption of the tractor with unbalanced trailer was found to be less than that with balanced trailer on all the three terrain surfaces in both the gears and throttle positions.